Status of Abortion Services in Jumla - Shrestha, Anjupa; Sharma, S. (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: Abortion was legalized in Nepal in September 2002. Only a trained and listed provider can provide abortion services at a health. For many women, especially in developing countries like Nepal, safe abortion may not be available, affordable or accessible despite the liberalization of abortion law. The aim of this study was to determine the status of abortion in Jumla.Methods: This retrospective study was conducted from the record of District Health Office; Jumla from the month of Ashad 2074 to Jestha 2075. Total Enumerative sampling technique was used. Data of public health sector and Marie Stopes Center, Jumla were retrieved and analyzed in terms of frequency, rate, and percentage.Results: Total 1196 women have received abortion services and abortion rate was 36.077 per 1000 (15-49 Years women). Most of the women(90%) were more than 20 years of age and majority of women (82%) chose medical method for abortion service. Majority (88.62%) have used Post abortion family Planning services.Conclusions: The abortion rate of Jumla was still high. Nine out of ten women who received abortion services were more than 20 years of age. Women preferred medical method rather than surgical method for abortion service. Nearly one tenth women had not used any post abortion family planning method.